El efecto de los altos costos en la producción en el subsector cultivo de tomate en el municipio de Tenza- Boyacá (2023)
The Tenza Valley area (Boyacá) has agroecological characteristics that have been favorable in the past for the development of tomato cultivation. The region has experienced progress in greenhouse tomato production, mainly with long-lived hybrids, since the end of the last century, which has generated agribusiness activity with great socioeconomic impact, which has been the reason for this research. Since by planting this product they have several harvests a year, small producers do not know how to cost their crops and, therefore, do not know the profit they obtain from their crops. This is reflected in the rise and fall of market prices for tomato growers in particular. You can identify the different production problems that must be faced every day due to the tensions between economic factors in the country, in which all socioeconomic practices and the various ways of presenting costs are considered. The research carried out has a deductive approach and qualitative research method, in which, through searching and collecting information from different primary and some secondary sources, it was possible to properly publicize the tomato production process and deduce its cost from a clear and easier to understand way,